Consent to transfusion: Patients' and healthcare professionals' attitudes towards the provision of blood transfusion information - Davis, R; Vincent, C; Sud, A; Noel, S; Moss, R; Asgheddi, M; Abdur-Rahman, I; Murphy, M (2012)
Background: Patients should be informed about the risks and benefits of blood transfusion and their consent should be documented. However, this is not routinely practised in the UK, and there have been few studies to investigate patients' and healthcare professionals' attitudes towards this process. Objectives: To investigate patients' and healthcare professionals' attitudes towards the information patients are provided with about transfusion and obtaining consent for transfusion. Measures: A cross-sectional qualitative survey design was employed. Attitudes towards transfusion-related information and consenting to transfusion were assessed using a patient survey and healthcare professional survey. Participants: One hundred and ten patients who had received a transfusion aged between 18 and 93 (60 males and 50 females) and 123 healthcare professionals (doctors, nurses and midwives) involved in administering transfusions. Results: Sixty-one patients recalled consenting transfusion. The majority said they were just told they needed a transfusion (N = 67) and only 1 patient said a full discussion about the risks and the benefits of the transfusion took place. However, although 82 patients said they were satisfied with the information, 22 patients reported they would have liked to have been given more details. The majority of healthcare professionals (N = 83) felt that patients were often not given sufficient information about transfusion. Conclusion: Greater efforts should be made to provide information to patients about the risks and benefits of blood transfusions. Future research should explore the most effective ways of delivering this information to patients in an appropriate and timely manner. © 2012 The Authors. Transfusion Medicine © 2012 British Blood Transfusion Society.